New insights into the regulation of the Saccharomyces cerevisiae UGA54 gene: Two parallel pathways participate in carbon-regulated transcription - Luzzani, C. (2007)
The Saccharomyces cerevisiae UGA4 gene, which encodes the γ-aminobutyric acid (GABA) and δ-aminolaevulinic acid (ALA) permease, is well known to be regulated by the nitrogen source. Its expression levels are low in the presence of a rich nitrogen source but are higher when a poor nitrogen source is used. In addition, GABA can induce UGA4 expression when cells are grown with proline but not when they are grown with ammonium. Although vast amounts of evidence have been gathered about UGA4 regulation by nitrogen, little is known about its regulation by the carbon source. Using glucose and acetate as rich and poor carbon source respectively, this work aimed to shed light on hitherto unclear aspects of the regulation of this gene. In poor nitrogen conditions, cells grown with acetate were found to have higher UGA4 basal expression levels than those grown with glucose, and did not show UGA4 induction in response to GABA. Analysis of the expression and subcellular localization of the transcription factors that regulate UGA4 as well as partial deletions and site-directed mutations of the UGA4 promoter region suggested that there are two parallel pathways that act in regulating this gene by the carbon source. Furthermore, the results demonstrate the existence of a new factor operating in UGA4 regulation. © 2007 SGM.